Investimento em segurança pública e políticas para as mulheres – da proposta orçamentária à aplicação dos recursos, em Palmas-TO - Carvalho, Gleidison Antônio de (Universidade Federal do Tocantins, 2017)
Violence against women and gender violence is recurrent in contemporary times. International and national laws are created, but the growth of violence to this vulnerable group still persists. However, public policy focused on the defense and protection of women, despite having pertinent legislation, existing bodies and forms of execution delineated, lack management visions more proper and public policies of budget and execution compatible with legal and doctrinal guidelines. Without the implementation of norms and rules, the attempt to make public policy effectively is innocuous. In this way, the research was carried out around the public budget for the state of Tocantins and Palmas, in the period from 2011 to 2015. He also had a semi-structured interview with managers of the Tocantins Military Police, Secretary of Citizenship and Justice, Secretariat of Public Security and Public Defender, who discussed issues such as budget management, articulation of the Contingency Network, agency performance and opportunities for improvement. women's public policy. The research was based on a both quantitative and qualitative approach and content analysis was used according to Bardin's (2009) methodological model. The results of the research showed that there are budgetary, logistical, human weaknesses and, above all, strategic visions. The articulations between the members of the Network are disconnected, sparse and individualized. The greater problem may not necessarily be in the availability of resources, but in the conception of public policy as a priority. As a result of the dissertation, a State Guideline was proposed for the PM to work with the Network against Violence against Women. The proposal serves not only for the state, but for the police institutions, since many of the states do not have guiding officers so that the police service does, in fact, lead to an institutional insertion of the police in the said Network of Confrontation. Allied to it, a change of conception may also occur, since violence against women goes beyond the legal issue. It goes from the perspective of gender reading. And understanding gender as a primary form of meaning of power relations is a proposition that goes beyond the binary definition of Man vs. Woman or even biological: part for discussion in a scenario where power is articulated, domain discussion appears.